HUBUNGAN STRES DENGAN SIKLUS MENSTRUASI PADA MAHASISWA AKADEMI KEBIDANAN SEMPENA NEGERI PEKANBARU - Ifni Wilda; Zurhayati Zurhayati (Ensiklopedia of Journal, 2023)
The menstrual cycle is a physiological change in a woman's body that occurs periodically and is influenced by reproductive hormones, ideally regularly every month with a period of 21-35 days each time the menstrual period begins. related to the menstrual cycle can be caused by psychological factors such as stressful situations and emotional disturbances. The purpose of this study was to determine the relationship between stress and the menstrual cycle in Sempena Negeri Pekanbaru Midwifery Academy students. This type of research is quantitative using correlation analysis. Cross-sectional research design, the population in this study were all students of the Sempena Negeri Pekanbaru Midwifery Academy with a total sample of 60 people. The instrument used to retrieve data is a questionnaire sheet. Univariate and bivariate data analysis using the Chi-Square Test. Based on the results of the Chi-Square Test, it showed that the results of the p-value = 0.000 and the degree of error α = 0.05, meaning that the results of the p-value ≤ 0.05, which shows that there is a relationship between stress and the menstrual cycle in Sempena Negeri Pekanbaru Midwifery Academy students. It is expected that midwifery education institutions will prepare various reference literature regarding the relationship between stress and the menstrual cycle in students.Keywords: Stress, Menstrual Cycle.